Artificial Organelles with Orthogonal‐Responsive Membranes for Protocell Systems: Probing the Intrinsic and Sequential Docking and Diffusion of Cargo into Two Coexisting Avidin–Polymersomes. Issue 11 (7th April 2021) - Wang, Xueyi; Moreno, Silvia; Boye, Susanne; Wang, Peng; Liu, Xiaoling; Lederer, Albena; Voit, Brigitte; Appelhans, Dietmar
Abstract: The challenge of effective integration and use of artificial organelles with orthogonal‐responsive membranes and their communication in eukaryotic protocells is to understand the intrinsic membrane characteristics. Here, a novel photo‐crosslinked and pH‐responsive polymersome (Psome B) with 2‐( N, N ′‐diisopropylamino)ethyl units in the membrane and its respective Avidin‐Psome B hybrids, are reported as good candidates for artificial organelles. Biotinylated (macro)molecules are able to dock and diffuse into Avidin‐Psome B to carry out biological activity in a pH‐ and size‐dependent manner. Combined with another polymersome (Psome A) with 2‐( N, N ′‐diethylamino)ethyl units in the membrane, two different pH‐responsive polymersomes for mimicking different organelles in one protocell system are reported. The different intrinsic docking and diffusion processes of cargo (macro)molecules through the membranes of coexisting Psome A and B are pH‐dependent as confirmed using pH titration–dynamic light scattering (DLS). Psome A and B show separated "open", "closing/opening", and "closed" states at various pH ranges with different membrane permeability. The results pave the way for the construction of multicompartmentalized protocells with controlled communications between different artificial organelles. Abstract : For studying orthogonal‐responsive membranes in eukaryotic protocells, artificial organelles are constructed by two different pH‐stable and pH‐responsive avidin–polymersome biohybrid structures. Different pH‐dependent "open", "closing/opening", and "closed" membrane states of the two coexisting biohybrid structures pave the way to different intrinsic and sequential docking and diffusion processes of cargo (macro)molecules in a pH‐ and size‐dependent manner.